Human development level as a modifier of education efficiency = Poziom rozwoju społecznego jako czynnik modyfikujący efektywność edukacji - Polcyn, Jan (Zielona Góra: Faculty of Economics and Management Press)
The aim of the study was to demonstrate the connection between education efficiency level and human development level. It was assumed that there is a connection between the value of Local Human Development Index (LHDI) and education efficiency established by means of the data envelopment analysis (DEA). The analysis covered data regarding 60 counties, recorded in 2013-2015. 30 counties with the highest Local Human Development Index (LHDI) and 30 counties with the lowest LHDI value were selected.
Keywords: rozwój społeczny; efektywność edukacji; ANOVA; human development; quality of education; effectiveness of education